Fashion designers' sketchbooks. - Davies, Hywel (London : Laurence King, 2010)
Juxtaposing the garments on the catwalk and in lookbooks with the original research material and with finished illustrations allows for a new perspective on the working methods of leading international designers and on the role of different media in the creation of their work, making the book a fascinating resource for both students and designers. Numerous leading designers, including John Galliano, Dries Van Noten, Antonio Marras for Kenzo, Yohji Yamamoto and Vivienne Westwood, are interviewed alongside their sketchbooks, discussing the roles they play in evolution of their work, and how they inform and encourage their creative processes. The result is in an inspirational overview of cutting-edge design today.
boek